Job burnout and work engagement in courier service organizations, Malaysia - an integration of job demands-resources model and theory of social exchange - Kong, Hoi Yoon (2019)
The growth of digital economy in Malaysia and worldwide countries will continue to contribute to the growth of courier service. The dispatch workers therefore are expected to be given higher workloads in terms of physical and psychological work commitment. Courier companies are experiencing higher staff turnover rate among the dispatch workers due to burnout and work engagement (WE) issues. The purpose of this study is to test the viability of current research model that integrates the JD-R model and theory of social exchange in explaining the dispatch workers’ reaction on job demands (JD), job resources (JR), and corporate volunteerism (CV) on their WE and burnout. The used of JD-R model in literature is not something new. However, compared to white collar workers, research on blue collar workers was limited. Blue and white collar workers may reacts differently on the dimensions of JD and JR. As burnout and WE behavior could influence a courier company’s key service: mail items delivery, it is thereby important to evaluate how the studied variables and its dimensions related to each other from the blue collar workers’ perspective. Multi-stage sampling method was employed so that the selected dispatch worker respondents could represent the population more accurately. Three hundred fifty completed questionnaires were collected from company’s assigned job dispatch workers. Covariance Based-SEM approach was used to test and confirm current study’s hypotheses. The result shows that JD and one of its dimension, physical demands related to burnout positively. Another dimension of the JD: psychological demands did not created significant direct effect on burnout. Job resources and one of its dimension, social support related to WE positively but another dimension of JR: decision latitude, had no significant effect on WE. In addition, dispatch workers who valued and understand the motive of corporate volunteering activities were more engaged to work hard. Although the JR’s dimension: decision latitudes did not create a direct significant effect on burnout, but the dimension construct had moderated the effects created by physical and psychological demands on burnout. The study results can provide useful indications to higher officials to address the issues related to job burnout and WE in the workplace. For example, to decrease burnout, appropriate levels of JD and physical demands should be designed. However, during peak delivery season, the assignment of higher JD and physical demands is inevitable. To moderate the effects of JD and physical demands on burnout, appropriate level of decision latitude (a dimension of JR) should be given, such as assigning specific job task that can map the respondent’s work interest or knowledge. In summary, the effectiveness of the provision of decision latitude’s element to workers depends on the company management’s objective. When the workers were given higher physical workload in specific time period, decision latitude will work in reducing burnout. However, during normal working circumstances, decision latitude will not be able to enhance the worker’s WE.